Direct pulp capping with mineral trioxide aggregate in a primary molar: a case report - Bodem, Oliver; Blumenshine, S.; Zeh, Debora; Koch, Martin Jean (International journal of paediatric dentistry, 2004)
A case is presented in which pulp capping was performed on a right first mandibular primary molar in a 7-year-old male patient. An alkaline cement powder based on mineral trioxide aggregate (MTA) was used for pulp capping. There were no pathological findings either on a radiograph taken after one year or on clinical examination after 18 months, and the right first mandibular primary molar remained vital after capping with MTA. Further clinical investigation of MTA for direct pulp capping of primary teeth should be performed.